Comparison of Circuit Training and Fartlek Methods on Cardiovascular Fitness in Relation to Motivation at SMAN 4 Tanjungpinang - Irfan Dwi Prasetyo; Bafirman Bafirman; Arsil Arsil; Padli Padli (JETL (Journal of Education, Teaching and Learning), 2025)
This study was prompted by initial observations revealing suboptimal maximal oxygen consumption (VO2max) levels in futsal athletes at SMA Negeri 4 Tanjungpinang. This diminished aerobic capacity is hypothesized to be influenced by multifactorial elements, notably the training methodologies employed and the athletes' levels of intrinsic and extrinsic motivation. Consequently, this research utilized a quasi-experimental, pretest-posttest control group design with a sample of 36 purposively selected students to empirically investigate the impact of these variables on VO2max enhancement. VO2max was assessed via the Yo-yo Intermittent Recovery Test Level 1 (Yo-yo IR1), while motivation data were gathered through a validated and reliable questionnaire. Two-way ANOVA with a 2x2 factorial design was employed for data analysis. Findings indicated a significant difference in VO2max between circuit training and fartlek training groups (Sig. = 0.028 < 0.05), and a significant interaction between training methods and motivation on VO2max (Sig. = 0.000 < 0.05). Furthermore, differences in VO2max were observed between circuit and fartlek training at both high (Qcount = 22.23 > Qtable 3.85) and low (Qcount = -8.83 < Qtable 3.85) motivation levels